2020
DOI: 10.1002/jmv.26198
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Epstein‐Barr virus DNA loads in high‐risk nasopharyngeal carcinoma families: Familial aggregation and host heritability

Abstract: Nasopharyngeal carcinoma (NPC), the most common head and neck cancer, is characterized by distinct geographic distribution and familial aggregation. Multiple risk factors, including host genetics, environmental factor, and EBV infection, have been linked to the development of NPC, particularly in the familial clustering cases. However, the cause of NPC endemicity remains enigmatic due possibly to the complicated interplay between these risk factors. Recently, positive Epstein‐Barr virus (EBV) DNA loads at naso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Moreover, we observed a trend toward a higher frequency of high-risk EBV subtypes in healthy individuals with NPC family history, compared with those without NPC family history. Previous studies of our labs also observed familial aggregation and high heritability of other EBV biomarkers, including EBV DNA loads of NP-brush and VCA-IgA antibody levels [11,12]. For example, we had observed significantly high heritability (h 2 =56.41 %, P=1.00×10 −7 ) of EBV DNA loads at nasopharyngeal in NPC high-risk families after adjusting co-habitation among family members [12].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Moreover, we observed a trend toward a higher frequency of high-risk EBV subtypes in healthy individuals with NPC family history, compared with those without NPC family history. Previous studies of our labs also observed familial aggregation and high heritability of other EBV biomarkers, including EBV DNA loads of NP-brush and VCA-IgA antibody levels [11,12]. For example, we had observed significantly high heritability (h 2 =56.41 %, P=1.00×10 −7 ) of EBV DNA loads at nasopharyngeal in NPC high-risk families after adjusting co-habitation among family members [12].…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies of our labs also observed familial aggregation and high heritability of other EBV biomarkers, including EBV DNA loads of NP-brush and VCA-IgA antibody levels [11, 12]. For example, we had observed significantly high heritability (h 2 =56.41 %, P =1.00×10 −7 ) of EBV DNA loads at nasopharyngeal in NPC high-risk families after adjusting co-habitation among family members [12]. Additionally, we had found VCA-IgA titre showed more significant correlation between both sibling pairs and parent–offspring pairs compared with spouse pairs [11].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“… 70 Recently, we found that nasopharyngeal EBV loads are positively correlated between relative pairs from NPC multiplex families and have significantly high heritability. 25 EBV infection status could modulate the role of genetic polymorphism in NPC. 71 However, laboratory evidence of the interaction between the etiological factors of NPC is lacking.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Therefore, the role of EBV life cycle in NPC tumorigenesis is complex. We recently found that the EBV loads at the nasopharyngeal site are correlated with each other among blood-relative pairs, and a significantly high heritability was also observed 25 within families with multiplex NPC cases, indicating that host genetics interacts with EBV in the development of NPC.…”
Section: Introductionmentioning
confidence: 99%